Value chain analysis of the aquaculture feed sector in Egypt - El-Sayed, A.F.M.; Dickson, M.W.; El-Naggar, G.O. (Elsevier, 2015)
This study was carried out to evaluate the value chain performance of the aquaculture feed sector in Egypt, in terms of value addition, employment and profitability. The strengths and weaknesses of each link of the value chain were assessed and appropriate upgrading, management and development strategies were suggested. Quantitative data were collected for each link in the value-chain through structured questionnaires that were drafted and distributed to the key players in the sector; 25 fish feed mills and 34 fish farms covering different geographical and production regions.